Synergistic Antitumor Effects of Caerin Peptides and Dendritic Cell Vaccines in a 4T-1 Murine Breast Cancer Model - Rongmi Mo; Junjie Li; Xinyi Song; Jiawei Fu; Mengqi Liu; Yuandong Luo; Quanlan Fu; Jinyi Wu; Hongyin Wu; Yongxin Liang; Tianfang Wang; Xiaosong Liu; et al. (Vaccines)
Background/Objectives: Breast cancer remains a leading cause of cancer-related mortality among women worldwide, necessitating novel therapeutic strategies. This study aimed to investigate the synergistic antitumor effects of caerin peptides (F1/F3) combined with dendritic cell (DC) vaccines in a 4T-1 murine breast cancer model, providing new insights for breast cancer immunotherapy. Methods: In vitro experiments evaluated the effects of F1/F3 on 4T-1 cell proliferation and apoptosis. A 4T-1 breast cancer mouse model was established, and treatments included F1/F3 alone, DC vaccines (DCV1: loaded with whole tumor antigens; DCV2: loaded with F1/F3-induced apoptotic antigens), or combination therapy. Flow cytometry analyzed immune cell subsets in the tumor microenvironment and lymph nodes, while ELISA measured cytokine levels. Results: F1/F3 significantly inhibited 4T-1 cell proliferation and induced apoptosis while suppressing tumor growth and lung metastasis in vivo. Flow cytometry revealed increased infiltration of CD4+ T cells and cDC1 in tumors, along with reduced PD-L1 expression. DCV2 exhibited stronger T-cell proliferation induction and lower IL-10 secretion in vitro. Combination therapy with DCV2 and F1/F3 demonstrated superior tumor suppression compared to monotherapy. Conclusions: F1/F3 enhances antitumor immunity by modulating the tumor microenvironment, and its combination with DCV2 yields synergistic effects. This study provides experimental evidence for combination immunotherapy in breast cancer, with potential for further optimization of DC vaccine design to improve efficacy.